ÁLCOOL E GRAVIDEZ: INFLUÊNCIA NA MORFOLOGIA FETAL - Fernanda Sardinha de Abreu Tacon; Kelly Cristina Borges Tacon; Waldemar Naves do Amaral (UniEVANGÉLICA, 2017)
Objective: knowing the risk factors may help in the elaboration of counseling programs for pregnant women and better conduct for health professionals, mainly due to the fact that their use is often concealed, making it difficult to follow. Data sourse: this systematic review study searched the Bireme, Scielo, PubMed, Lilacs and Site Up to Date databases. The selection took into account the titles and abstracts related to the subject, from 2010 to 2017, using the descriptors alcohol / ethanol, pregnancy / pregnancy and fetal development / fetal morphology. We found 70 articles, of these were selected 35, the most recent and high theoretical content required for the construction of the text. Data synthesis: through this analysis, we observed the need for early identification of alcohol consumption in pregnancy, not only the maternal report. Conclusions: therefore, new research in the area is necessary for better prevention and adaptation of the patient after a diagnosis of Fetal Alcohol Spectrum Disorders and to adopt prophylactic measures in order to protect the fetus and pregnant women, contributing to the improvement of public health